The Ontario Universal Typing of Tuberculosis (OUT-TB) Surveillance Program – What It Means to You - Shelly Bolotin; David C Alexander; Jennifer L Guthrie; Steven J Drews; Frances Jamieson (Canadian Respiratory Journal)
BACKGROUND: Tuberculosis (TB) is a serious disease that is transmitted primarily by the airborne route. Effective disease control and outbreak management requires the timely diagnosis, isolation and treatment of infected individuals with active disease; contact tracing to identify secondary cases likely to benefit from treatment of latent infection; and laboratory identification or confirmation of epidemiologically linked cases. TB genotyping enables the comparison of Mycobacterium tuberculosis complex (MTBC) strains and the identification of cases that may or may not be linked. The increased availability of molecular methods for genotyping has allowed for greater discrimination of MTBC strains and greatly enhanced understanding of TB transmission patterns.